THEORETICAL AND PRACTICAL ASPECTS OF PRODUCTION MODERNIZATION IN HORTICULTURE - Siddikov Zohid To’lkinivich; Mardiyev Nurali; Achilov Mashrab Ulugbekovich (Scholar Express Journals, 2023)
The article reveals, in detail, the theoretical aspects of modernization of production in horticulture, having studied the point of view of many scientists, the author's definition of modernization of production is given. The factors influencing the modernization of production in horticulture are systematized and scientifically substantiated, dividing them into three groups according to the nature of their origin. Practical recommendations and proposals have been developed for the modernization of production in horticulture in the future
Keywords: modernization; fruit and vegetable sector; regulatory documents; innovation